Responses to solar ultraviolet-B radiation in a shrub-dominated natural ecosystem of Tierra del Fuego (southern Argentina) - Rousseaux, Maria Cecilia; Scopel, Ana Leonor; Searles, Peter Stoughton; Caldwell, Martyn M.; Sala, Osvaldo Esteban; Ballare, Carlos Luis (Global Change Biology)
A study was made of the effects of solar ultraviolet-B radiation (UV-B) on the growth of the dominant plant species of a shrub-dominated ecosystem in Tierra del Fuego. This part of southern Argentina can be under the direct influence of the Antarctic 'ozone hole' during the austral spring and lingering ozone-depleted air during the summer. The plant community is dominated by an evergreen shrub (Chiliotrichum diffusum) with an herbaceous layer of Gunnera magellanica and Blechnum penna-marina in the interspaces between the shrubs. Inspections of ozone trends indicate that the springtime and summertime ozone column over Tierra del Fuego has decreased by 10-13% from 1978/9 to 1998/9. In a set of well-replicated field plots, solar UV-B was reduced to approximately 15-20% of the ambient UV-B using plastic films. Polyester films were used to attenuate UV-B radiation and UV-transparent films (∼90% UV-B transmission) were used as control. Treatments were imposed during the growing season beginning in 1996 and continued for three complete growing seasons. Stem elongation of the shrub C. diffusum was not affected by UV-B attenuation in any of the three seasons studied. However, frond length of B. penna-marina under attenuated UV-B was significantly greater than that under near-ambient UV-B in all three seasons. Attenuation of solar UV-B also promoted the expansion of G. magellanica leaves in two of the growing seasons. Differences between treatments in leaf or frond length in B. penna-marina and G. magellanica did not exceed 12%. Another significant effect of UV-B attenuation was a promotion of insect herbivory in G. magellanica, with a 25-75% increase in the leaf area consumed. Changes in plant phenology or relative species cover were not detected within the time frame of this study. The results suggest that the increase in UV-B radiation associated with the erosion of the ozone layer might be affecting the functioning of this ecosystem to some degree, particularly by inhibiting the growth of some plant species and by ...